Gene Therapy for the Induction of Chimerism and Transplant Tolerance - Gunthart, Mirja; Kearns-Jonker, Mary (Current Gene Therapy, 2007)
Technical advances in transplant surgery and the development of powerful and effective immunosuppressive drugs have contributed to the success of organ transplantation as a medical treatment for patients with end-stage diseases. Associated with this procedure, however, is a dependence on life-long immunosuppressive drugs, which are required to prevent graft rejection. These agents render the patient susceptible to infections, tumors and various side affects. The ability to achieve tolerance to organ grafts would free transplant patients from lifelong dependency on pharmacological agents with harmful side effects. Several laboratories have shown that tolerance can be achieved by the induction of mixed cell chimerism and/or by molecular chimerism achieved by gene transfer techniques prior to graft placement. Molecular chimerism, induced by transplantation of autologous bone marrow expressing either allo- or xenoantigens has the potential to induce tolerance without the development of graft vs. host disease. The application of gene transfer techniques to induce chimerism has been shown to reshape the immune repertoire by mechanisms that include clonal deletion, the induction of central tolerance or generation of regulatory T cells that would eliminate the need for immunosuppressive drugs. Optimization of this methodology for clinical use could therefore revolutionize the field of transplantation. This review summarizes the recent studies which have compared the efficacy of different vectors, conditioning regimens, and transduction conditions leading to new and improved techniques for the application of gene therapy to induce chimerism and transplant tolerance to both allografts and xenografts.
Keywords: immunization